?LIPID FRACTIONS AND FATTY ACID COMPOSITION OF TRIANTHEMA PORTULACASTRUM LINN (Biological Sciences - PJSIR, 1996)
Trianthema portulacastrum seed oil (12.5 %) has been examined for its physico-chemical characteristics and fatty acid composition. Thin layer chromatography of the oil into lipid classes resulted into polar lipids (4.8%) and neutral lipids (95.2 %). Fractionation of the neutral lipids provided hydrocarbons (0.3 %), wax esters (0.5 %), sterol esters (4.0 %), triglycerides (84.5%), free fatty acids (1.8 %), diglycerides (2.5 %) and monoglycerides (1.6 %). The fatty acids which ranged from C, to C20 have also been reported.